EXPRESSION OF PLASMODIUM FALCIPARUM ERYTHROCYTE â BINDING ANTIGEN (PFEBA140) REGION III â V IN ESCHERICHIA COLI - Hayyi Azhari, Dena
Malaria is a disease caused by infection with parasitic protozoa of the genus Plasmodium transmitted by the bite of female mosquitoes of the genus Anopheles. Erythrocyte Binding Antigen 140 (EBA140) is one of the proteins on Plasmodium falciparum merozoites that plays a role in the process of erythrocyte cell invasion involving specific interactions between merozoite ligands and glycophorin C (GPC) as the main receptor of malaria parasites on the surface of erythrocyte cells. EBA140 RIII-V has the ability to induce immune responses and can inhibit parasite growth in vitro so that it has the potential to become a malaria vaccine candidate. The purpose of this study was to construct a recombinant plasmid for the expression of the PfEBA140 RIII-V gene in Escherichia coli (E. coli). The research stages carried out were (i) amplification of the PfEBA140 RIII-V gene (ii) construction of plasmid pET-16b-PfEBA140 RIII-V (iii) transformation of recombinant plasmid pET-16b-PfEBA140 RIII-V in three strains of E. coli, namely E. coli BL21 (DE3), E. coli BL21 CodonPlus (DE3)-RIPL, and E. coli Arctic express (DE3) (iv) expression of recombinant PfEBA140 RIII-V protein in host E. coli. The PfEBA140 RIII V gene was amplified using genomic DNA template isolated from P. falciparum isolate Jayapura by Polymerase Chain Reaction (PCR) method. The primer pairs used were forward primer 5' - CCG CTC GAG GGT GAT GGA ACG CCA ATA AG - 3' and reverse primer 5' - CGC GGA TCC CCT TTC GTC AGA ATA GGT ACA - 3' with a annealing temperature of 59.4 ? resulting in amplicons measuring 930 pb. The amplification results of PfEBA140 RIII-V were then cloned into the pGEM-T Easy cloning vector resulting in recombinant plasmid pGEM-T-PfEBA140 RIII-V. Subcloning of the PfEBA140 RIII-V gene into the pET-16b expression vector using XhoI and BamHI restriction enzyme pairs resulted in the recombinant plasmid pET-16b-PfEBA140 RIII-V. Confirmation of successful cloning and subcloning was proven by colony PCR, restriction analysis, and sequencing. The recombinant plasmids were transformed into three E. coli strains, namely E. coli BL21 (DE3), E. coli BL21 CodonPlus (DE3)-RIPL, and E. coli Arctic express (DE3) using the heat shock method. The PfEBA140 RIII-V gene was expressed in E. coli BL21 (DE3) and E. coli BL21 CodonPlus (DE3)-RIPL with expression conditions; IPTG concentration of 0.5 mM, induction time of 4 hours at 37?, 150 rpm. While expression in E. coli Arctic express (DE3) uses an induction time of 18 hours at 10?. Protein expression results were analyzed by SDS-PAGE and western blot method using anti-His-tag antibody. Based on SDS-PAGE and western blot analysis, it was concluded that the protein was successfully expressed in E. coli BL21 CodonPlus (DE3)-RIPL with a molecular weight of ~55 kDa. In conclusion, in this study, pET-16b-PfEBA140 RIII-V was successfully constructed and the PfEBA140 RIII-V gene was successfully expressed in E. coli BL21 Codon Plus (DE3)-RIPL as soluble protein and inclusion body.